Transvenous lead extraction procedures in women based on ESC-EHRA EORP European Lead Extraction ConTRolled ELECTRa registry: is female sex a predictor of complications?. Issue 12 (30th October 2019) - Polewczyk, Anna; Rinaldi, Christopher A; Sohal, Manav; Golzio, Pier-Giorgio; Claridge, Simon; Cano, Oscar; Laroche, Cécile; Kennergren, Charles; Deharo, Jean-Claude; Kutarski, Andrzej; Butter, Christian; Blomström-Lundqvist, Carina; et al.
Abstract: Aims: Female sex is considered an independent risk factor of transvenous leads extraction (TLE) procedure. The aim of the study was to evaluate the effectiveness of TLE in women compared with men. Methods and results: A post hoc analysis of risk factors and effectiveness of TLE in women and men included in the ESC-EHRA EORP ELECTRa registry was conducted. The rate of major complications was 1.96% in women vs. 0.71% in men; P  = 0.0025. The number of leads was higher in men (mean 1.89 vs. 1.71; P  < 0.0001) with higher number of abandoned leads in women (46.04% vs. 34.82%; P  < 0.0001). Risk factors of TLE differed between the sexes, of which the major were: signs and symptoms of venous occlusion [odds ratio (OR) 3.730, confidence interval (CI) 1.401–9.934; P  = 0.0084], cumulative leads dwell time (OR 1.044, CI 1.024–1.065; P  < 0.001), number of generator replacements (OR 1.029, CI 1.005–1.054; P  = 0.0184) in females and the number of leads (OR 6.053, CI 2.422–15.129; P  = 0.0001), use of powered sheaths (OR 2.742, CI 1.404–5.355; P  = 0.0031), and white blood cell count (OR 1.138, CI 1.069–1.212; P  < 0.001) in males. Individual radiological and clinical success of TLE was 96.29% and 98.14% in women compared with 98.03% and 99.21% in men ( P  = 0.0046 and 0.0098). Conclusion: The efficacy of TLE was lower in females than males, with a higher rate of periprocedural major complications. The reasons for this difference are probably related to disparities in risk factors in women, including more pronounced leads adherence to the walls of the veins and myocardium. Lead management may be key to the effectiveness of TLE in females.